Using Multimedia in the Classroom and Evaluating Its Effectiveness Using Kirkpatrick’s Principles - Che Embi, Zarina; Neo, Tse Kian; Neo, Mais (INTI International University, 2011)
For decades, the prevalent teaching method has been the traditional face-to face method and it is still being used in today’s classrooms. Though it has been effective, it is considered limited in today’s fast- paced and digital world. With the introduction of multimedia and ICT, the teaching process has become more flexible and has shifted from learning about technology to teaming with technology. Therefore, a myriad of ICT-based Instructional strategies are now available for the teacher to use. The use of multimedia technology in the classroom has changed the manner in which teachers teach and students learn. As such, technology through the use of the Internet and the World Wide Web has made students’ access to knowledge more convenient and flexible. In order to evaluate its effectiveness in the classroom, Kirkpatrick’s mode4 for evaluation was used. Since Its Introduction in 1959, Kilpatrick’s four Level model has been used extensively to evaluate training programs and as the basis for evaluation of a variety of educational settings. Therefore, this research seeks to study the effects on the students’ learning process when multimedia-based instructions are used and to evaluate their effectiveness according to Kirkpatrick’s Levels of evaluation. The study was conducted in Multimedia University where multimedia technology was used to enhance the student’s learning. Data were collected through pre-tests and posttests, surveys and questionnaires and were later analyzed. The study assesses the effects on the student learning as well as their perceptions in this learning environment. The findings are based on using Kirkpatrick’s principles of teaming evaluation. The results were positive and encouraging as the students were able to enhance their learning process while being motivated and enjoyed teaming in this environment.